Fine-tuning the practical relevance of a quality framework for integrated nature-based interventions in healthcare facilities. A qualitative interview study - Sterckx, Ann; Delbaere, Ben; De Blust, Geert; Spacova, Irina; Samson, Roeland; Van den Broeck, Kris; Remmen, Roy; Keune, Hans (Frontiers in Public Health, 2024)
Integrated nature-based interventions in healthcare facilities are gaining importance as promising health and biodiversity promotion strategies. This type of intervention combines the restoration of biodiversity in the vicinity of the healthcare facility with guiding patients in that natural environment for health outcomes. However, quality appraisal of these interventions is still poorly developed. To address this, the authors of a recent scoping review have developed a preliminary quality framework to support healthcare facilities in designing, implementing, and evaluating these interventions. This study aims to refine the practical relevance of this framework within emerging practices. A qualitative interview study was conducted in seven healthcare facilities in Belgium, involving 22 professionals, through a combination of snowball and purposive sampling. Participants included nature management coordinators, healthcare professionals and managers. Semi-structured interviews were transcribed and analyzed using NVivo. Both deductive and inductive thematic analyses were employed to explore the framework's practical relevance. Additionally, the study included a stakeholders' assembly review and member checking of the findings. The contextualization and complexity of integrated nature-based interventions demonstrated the need for an evidence-based quality framework describing nature-based interventions. The study led to nine quality criteria, confirming the eight quality criteria derived from a previous scoping review, and the identification of a new quality criterion 'Capacity building, leverage and continuity'. These quality criteria have been refined. Finally, a proposal for a quality framework was developed and operationalized in a checklist. Deployment of the quality framework should be embedded in a continuous cyclical, adaptive process of monitoring and adjusting based on evaluations at each phase of an integrated nature-based intervention. Bridging the domains of healthcare and nature management in the context of an integrated nature-based intervention in a healthcare facility requires a transdisciplinary approach. Scientific frameworks such as "complex interventions", Planetary Health and One Health can support the co-design, implementation and evaluation of integrated nature-based interventions within a cyclical, adaptive process. In addition, the importance of the quality of the interactions with nature could gain from more sophisticated attention. Finally, the implications for healthcare facilities, policymakers and education are discussed, as well as the strengths and limitations of the study.